1986
DOI: 10.1080/0013191860380106
|View full text |Cite
|
Sign up to set email alerts
|

Dark‐interval‐threshold and Reading and Listening Comprehension in Nine‐year‐old Children

Abstract: Sixty nine-year-old children were grouped within sexes into three levels of dark-interval-threshold (DIT), and then both read and listened to easy and difficult prose passages which were followed by comprehension questions. A significant interaction was found between DIT, mode of presentation (reading or listening) and level of difficulty on their effect on comprehension. Generally, comprehension decreased with DIT although this was less marked when listening to the difficult material. The finding indicates th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

1986
1986
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
0
3
0
1
Order By: Relevance
“…Since reading technique is likely to change with increasing age from one word at a time to scanning of sentences for meaning (see, for example, Goodman 1967) it became apparent that DIT was probably not a purely visual process but a manifestation of a more central characteristic of the information processing system. In view of this, Riding and Pugh (1986) investigated the relationship between DIT and both reading and listening comprehension, and found that DIT was related to both in a fairly similar manner confirming that the effect was not limited to the visual system.…”
Section: Msume Seuil D 'Intervalle Noir (Dit) Niveau D'intensitc! Lumentioning
confidence: 63%
See 3 more Smart Citations
“…Since reading technique is likely to change with increasing age from one word at a time to scanning of sentences for meaning (see, for example, Goodman 1967) it became apparent that DIT was probably not a purely visual process but a manifestation of a more central characteristic of the information processing system. In view of this, Riding and Pugh (1986) investigated the relationship between DIT and both reading and listening comprehension, and found that DIT was related to both in a fairly similar manner confirming that the effect was not limited to the visual system.…”
Section: Msume Seuil D 'Intervalle Noir (Dit) Niveau D'intensitc! Lumentioning
confidence: 63%
“…In view of the finding of Riding and Pugh (1986) of a relationship between DIT and both reading and listening comprehension, the effect is not restricted to the visual system. For subjects having a short persistence the visual or auditory signal of a word will fade very quickly which may cause some of the words to be lost.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations